The C-terminal domain of connexin43 modulates cartilage structure via chondrocyte phenotypic changes - Gago-Fuentes, Raquel (Oncotarget, 2016)
Chondrocytes in cartilage and bone cells population express connexin43 (Cx43) and gap junction intercellular communication (GJIC) is essential to synchronize cells for coordinated electrical, mechanical, metabolic and chemical communication in both tissues. Reduced Cx43 connectivity decreases chondrocyte differentiation and defective Cx43 causes skeletal defects. The carboxy terminal domain (CTD) of Cx43 is located in the cytoplasmic side and is key for protein functions. Here we demonstrated that chondrocytes from the CTD-deficient mice, K258stop/Cx43KO and K258stop/K258stop, have reduced GJIC, increased rates of proliferation and reduced expression of collagen type II and proteoglycans. We observed that CTD-truncated mice were significantly smaller in size. Together these results demonstrated that the deletion of the CTD negatively impacts cartilage structure and normal chondrocyte phenotype. These findings suggest that the proteolytic cleavage of the CTD under pathological conditions, such as under the activation of metalloproteinases during tissue injury or inflammation, may account for the deleterious effects of Cx43 in cartilage and bone disorders such as osteoarthritis.